THE INFLUENCE OF LIFESTYLE, PRICE, BRAND IMAGE, PACKAGING QUALITY AND PRODUCT QUALITY ON PURCHASE INTEREST OF STARBUCKS CANNED PRODUCTS CUSTOMERS - Zakaria Zakaria; Nur Aisyah Qadri Saiful; Ekbal Santoso; Nova Erliyana; Eva Yuniarti Utami (Sean Institute, 2023)
This study aims to examine the relationship between variables, especially variables that influence purchase intention such as brand image, product quality, lifestyle, price, and packaging. This type of research is called quantitative research. This study used a non-probability sampling strategy for data collecting. This survey included 100 respondents in total. Multiple linear regression analysis was used to analyze the survey results. The analysis's findings indicate that brand image, product quality, lifestyle, price, and packaging all simultaneously influence purchase intention, with product quality, lifestyle, price, and packaging having a greater influence than brand image and packaging.